Precompression of soft soils by surcharge preloading: Some common pitfalls and misunderstood fundamentals - Ramli, Mohamad, Dato' Assoc. Prof. (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/